Influence of meteorological phenomena on resilience of Gorgan spruce forests in the Ukrainian Carpathians - Zeinalian, A. M.; Oliinyk, V. S. (Forestry and Forest Melioration, 2021)
Introduction One of the most pressing problems of mountain forestry in the Ukrainian Carpathians is to strengthen the resilience of spruce forests, which are vulnerable to modern global warming with the intensification of harmful meteorological phenomena. European spruce (Picea abies (L.) H. Karst.) positively influences the forest environment and has high productivity. However, it is vulnerable to snow and windbreaks. In recent decades, the massive decline of spruce trees has added to the adverse natural processes. Therefore, knowledge of the distribution patterns of harmful abiotic factors in the forests and their impact on the stability of stands is important for the development of measures to prevent disasters. Materials and Methods Assessment of the impact of harmful meteorological phenomena on the resilience of spruce trees was based on: (1) generalization of publications on the occurrence of disasters in forests; (2) analysis of data on 413 sites in stands, damaged and prescribed for sanitary felling due to dieback and windbreaks in 2011-2020 in the Gorgan mountain range. These data represented all the forest biodiversity of the Carpathians in the altitude range of 300–1,450 m above sea level. Results Increasing hypsometric levels change both the distribution areas of forest vegetation and the number of meteorological phenomena influencing forest resilience. In the foothills and low-mountains (300–800 m) with oak, fir and beech forest types, the number of harmful phenomena is 6–7; in mountainous mixed spruce forests (900–1,200 m), it is reduced to 4-5, and in pure natural spruce forests (above 1200 m), the number is 2–3. In general, the spruce, being sensitive to extreme weather conditions, can be the most affected outside its natural range in sites where it is a derivative species. In the range of spruce forests, derivative spruce forests have on average 25% lower resistance to harmful meteorological phenomena as compared to the native stands. Outside the range, this ratio can reach even 5–11 times. Such permanent phenomena as windbreaks and dieback of spruce forest have the most harmful and large-scale consequences for forestry. The maximal influence of windbreaks is typical for heights of 850–1,100 m and of spruce dieback for levels of 650–800 m. Decline foci in spruce forests are places of intensified windbreaks. Compared to the impact of windbreaks and spruce dieback on forests, the harmful effects of other natural disasters on the area and volume of damaged wood are 5-20 times less. Conclusions Secondary spruce forests at 300–900 (1,000) m above sea level are the most vulnerable to the effects of harmful natural phenomena, the main consequences of which are the permanent and large-scale dieback and windbreaks. The development of these processes is also influenced by relief and soil conditions. In the current weather conditions, the appearance of almost 75% of windbreak foci is possible in spruce dieback areas. Regularities of natural disaster distribution in the mountains should be taken into account in forest management to increase the resilience of forests in the Carpathian region.